109 Flavored tobacco sales restrictions and e-cigarette use among high school students in California - Melanie Dove; Kevin Gee; Elisa Tong (Journal of Clinical and Translational Science, 2022)
OBJECTIVES/GOALS: Flavored tobacco sales restrictions (FTSRs) are implemented to reduce access to flavored tobacco products. We examined the association between seven local FTSRs implemented in 2018/2019 and e-cigarette use among high school students in the Bay Area region of California. METHODS/STUDY POPULATION: We analyzed data from the California Healthy Kids Survey using a difference-in-differences (D-I-D) strategy. We compared pre- and post-policy changes one year after implementation in current tobacco use (e-cigarettes and cigarettes) among students exposed (n=20,832) versus unexposed (n=66,126) to a FTSR. Exposed students attended school in a city with a FTSR. Other outcomes included ever use of e-cigarettes, ever marijuana use in an e-cigarette, and ease of access to e-cigarettes. RESULTS/ANTICIPATED RESULTS: Pre- to post-policy, current tobacco use did not change in exposed students (e-cigarette: 10.5% to 11.1%; cigarette 2.6% to 2.5%) and decreased in unexposed students (e-cigarette: 12.8% to 11.4%; cigarette: 2.2% to 1.7%). FTSRs were not associated with a change in odds of current e-cigarette (adjusted D-I-D OR: 1.25, 95% CI: 0.95, 1.65) or cigarette use (adjusted D-I-D OR: 1.24, 95% CI: 0.94, 1.63), relative to unexposed students. For both exposed and unexposed groups, there was a 54-57% increased odds of reporting ease of access to e-cigarettes and a 29-35% increased odds of ever using marijuana in an e-cigarette. No change was detected for ever e-cigarette use. DISCUSSION/SIGNIFICANCE: Local FTSRs in California were not associated with a decrease in e-cigarette or cigarette use one-year post-implementation. Increased ease of access and marijuana use may be explanatory factors.